Four-dimensional characterization of a PFOA-contaminated fractured rock aquifer (FRA) in Bennington, Vermont, U.S.A - Kim, Jonathan J.; Ryan, Peter C.; Schroeder, Timothy; Romanowicz, Edwin; Boutt, David; Belaval, Marcel; Shanley, James (Frontiers in Water, 2023)
Between 2016 and 2019, the Vermont Department of Environmental Conservation discovered that groundwater from over 50% (355/628) of wells and springs in the Bennington area had perfluorooctanoic acid (PFOA) concentrations > 20 parts/trillion (ppt) (Vermont action level). The distribution of contaminated wells was complex, with very different PFOA concentrations in closely-spaced wells (<100 m apart). PFOA was introduced into the environment by a factory that produced Teflon™-coated fabrics from about 1978–2002. Manufacturing involved PFOA expulsion from smokestacks followed by atmospheric transport, deposition, and downward leaching to the aquifer system. The fractured rock aquifer was characterized through physical components (geologic mapping, spatial analysis of wells, and geophysical logging) to build a Three-dimensional conceptual model and then map the spatial distribution of chemical groundwater tracers (PFOA, major and trace elements, stable isotopes, and and recharge ages), adding a fourth temporal dimension. The field area consists of four imbricated metamorphic rock slices bounded by thrust faults. The dominant fracture sets that overprint these slices control the N-S and E-W topographic “grain.” Geophysical logging divided wells into those completed internal to or on the margins of thrust slices. Major and trace element analysis shows that groundwater can be spatially discriminated into carbonate (TDS, Ca, Mg, HCO3), shaly (Sr, U, SO4), and siliceous (K, Si) groups. Depleted H2O stable isotope signatures characterize the siliceous group. Recharge-ages determined from CFC11, 12, and 113 and tritium correlate with geochemical groups and were divided into “older” (~1953–73) and “younger” (1963–88), which predate and are synchronous with factory operation, respectively. Our conceptual model shows recharge from highlands to the west and east flowing toward the Bennington valley where it is locally tapped by wells along thrust faults or fracture zones. This water has older recharge ages and anomalously low PFOA concentrations (<6.7 ppt in 12 of 15 samples, mean = 7.9 ppt) compared to the majority of wells in this region, which are completed in the internal portions of thrust slices. These wells contain groundwater with younger recharge ages and high PFOA concentrations (mean = 290 ppt) and occurrence (>20 ppt in 28/36 samples), indicating mixing of younger and older waters.